(846) On The Measurement of Economic Growth: an unbiased index number for homogeneous utility functions حول قياس النمو الاقتصادي: رقم قياسي غير متحيز لدوال المنفعة المتجانسة - Moheb Ghali. (INP, 2024)
The past two decades have seen significant advancements in the theory of economic development, leading to a rapid expansion of literature in this field. Early research focused on defining and measuring economic growth while highlighting the limitations of various approaches. Standard economic texts now emphasize GDP, national income, or per capita income as key indicators of material welfare, despite challenges in cross-country and intertemporal comparisons. A crucial aspect of economic analysis is measuring growth rates, which are often deemed more comparable than absolute levels. This paper explores one such method—constructing a welfare-based index—to assess and compare growth rates across different contexts.